qFD: Coherent and Depolarizing Fault Diagnosis for Quantum Processors - Li, Yen-Wei; Hsieh, Cheng-Yun; Wu, Meng-Chen; Li, James Chien-Mo (Proceedings - International Test Conference, 2024)
Errors caused by faults would strongly affect the correctness of noisy intermediate-scale quantum (NISQ) circuits. In this work, we propose a technique for diagnosing coherent and incoherent faults for NISQ circuits. The proposed technique contains three phases: rough diagnosis, fine diagnosis, and depolarizing diagnosis. Rough diagnosis grid searches the Bloch sphere to locate an approximate range of a coherent fault. Fine diagnosis then precisely locates the coherent fault size based on the narrowed-down search space. At last, depolarizing diagnosis measures the depolarizing fault size. We demonstrate our technique using the Qiskit simulator with noise-free and noisy backends. The diagnosis accuracy between the diagnosed faulty gates and the injected faulty gates is over 99.95%, which is better than traditional quantum process tomography under the same conditions. Our results show that the diagnosis error of coherent faults does not affect the diagnosis accuracy of depolarizing faults. Experiments on the IBM Q devices have also been performed, and results of over 99.83% diagnosis accuracy show that our technique still preserves good resolution on real quantum circuit devices.